PENGUATAN KAPASITAS DESA TANGGUH BENCANA UNTUK PENGURANGAN RISIKO BENCANA DI DESA PENDUA KECAMATAN KAYANGAN KABUPATEN LOMBOK UTARA - Saori, Umi; Ulfa, Nasya; Hamsi, Saida; Ziyadi, Mohamad Naufal; Irawan, Randi Ade; Fuady, Rifqy Novandi Putera; Karinda, Putri; Safitri, Nur; Sarisuta, Made Grace Ayu; Surya, Muhammad Dianku; Teluma, Aurelius Rofinus Lolong (Jurnal Wicara, 2024)
The earthquake disaster in Pendua Village, Kayangan District, North Lombok Regency that occurred in 2018 has given rise to various problems. The community's unpreparedness in facing the earthquake disaster gave rise to social and economic impacts. The aim of this service is to help the community increase their knowledge, abilities and independence in facing and overcoming disaster problems after the Earthquake. The method used is by conducting outreach and training on disaster mitigation as well as providing the community with education on how to utilize local food resources to improve the economy of the Pendua Village community. The first benchmark for the success of this activity is increasing knowledge about disasters and how to deal with them among community groups. Second, increasing the ability of community groups to optimize natural resources in the form of local food as a forum for the community to produce products of economic value.